Research Progress of circRNAs in Head and Neck Cancers - Li, Panchun; Zhu, Kunjie; Mo, Yongzhen; Deng, Xiangying; Jiang, Xianjie; Shi, Lei; Guo, Can; Zhang, Wenling; Zeng, Zhaoyang; Li, Guiyuan; Xiong, Wei; Zhang, Shanshan; et al. (Frontiers in Oncology, 2021)
Circular RNAs (circRNAs) are a novel type of non-coding RNAs. Because of their characteristics of a closed loop structure, disease- and tissue-specificity, and high conservation and stability, circRNAs have the potential to be biomarkers for disease diagnosis. Head and neck cancers are one of the most common malignant tumors with high incidence rates globally. Affected patients are often diagnosed at the advanced stage with poor prognosis, owing to the concealment of anatomic sites. The characteristics, functions, and specific mechanisms of circRNAs in head and neck cancers are increasingly being discovered, and they have important clinical significance for the early diagnosis, treatment, and prognosis evaluation of patients with cancer. In this study, the generation, characteristics, and functions of circRNAs, along with their regulatory mechanisms in head and neck cancers have been summarized. We report that circRNAs interact with molecules such as transcription and growth factors to influence specific pathways involved in tumorigenesis. We conclude that circRNAs have an important role to play in the proliferation, invasion, metastasis, energy and substance metabolism, and treatment resistance in cancers.